Charlie and the chocolate factory [videorecording (DVD)] - Burton, Tim, 1958-; Depp, Johnny; Highmore, Freddie, 1992-; Kelly, David, 1929-2012; Bonham Carter, Helena, 1966-; Taylor, Noah; Dahl, Roald (Warner Home Video, 2005)
Charlie and five others draw golden tickets from Wonka chocolate bars and win a guided tour of the legendary candy factory that no outsider has seen in 15 years. Dazzled by one amazing sight after another, Charlie is drawn into Wonka's fantastic world.